Research progress and prospects on glass-ceramics prepared from ferronickel slag - Zhiqiang Yang; Zhiyun Ji; Xiaohui Fan; Min Gan; Zhaolei Deng; Yuanjie Zhao; Xiaoxian Huang; Zengqing Sun; Xuling Chen; Zhenxiang Feng (Journal of Environmental Chemical Engineering, 2026)

Research progress and prospects on refractory materials prepared from high-carbon ferrochrome slag: A review - Zhiqiang Yang; Zhiyun Ji; Xiaohui Fan; Min Gan; Qiang Li; Yuanjie Zhao; Xiaoxian Huang; Zengqing Sun; Xuling Chen; Zhenxiang Feng (Process Safety and Environmental Protection, 2026)

PICK1 modulates the proliferation and migration of gastric cancer cells by regulating TLR4 - Kaiqiang Li; Yimin Yang; Yaling Wang; Jing Jin; Qianni Wang; Lina Peng; Aibo Xu; Xuling Luo; Wei Yang; Peng Xu; Bingyu Chen; Ke Hao; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Co-treatment of water-washed MSWI fly ash in iron ore sintering process: Removal behavior of typical heavy metals and regulation technology - Xiaolong Wang; Zhiyun Ji; Binbin Huang; Xiaohui Fan; Min Gan; Zengqing Sun; Xuling Chen (Journal of Environmental Chemical Engineering, 2025)

Resourceful utilization of combustible solid wastes throughout steelmaking processes: Recent progress and prospects - Zhiyun Ji; Dan Yu; Xiaohui Fan; Min Gan; Dan Zhang; Xiaoxian Huang; Zengqing Sun; Xuling Chen; Xiaolong Wang; Penghui Ping (Journal of Cleaner Production, 2024)

Flexible and MOF-808 uniformly assembled polyimide nanofiber membranes with excellent mechanical properties for rapid degradation of chemical warfare agents - Zhikang Cheng; Xiang Li; Li Zhang; Zupei Yuan; Haimin Zheng; Hao Guo; Xu Zhao; Jie Chen; Yu Pan; Xiaoxiao Chen; Yanlai Feng; Zhouai Luo; et al. (Chemical Engineering Journal, 2023)

Comprehensive evaluation of hydrogen-rich energy application in iron ore sintering process: Deep function mechanism analysis and process optimization - Yufeng Wu; Xiaohui Fan; Zhiyun Ji; Min Gan; Dan Yu; Zengqing Sun; Xuling Chen; Lincheng Liu; Xiaoxian Huang; Jinhua Li (Journal of Cleaner Production, 2023)

Threat of soil formation rate to health of karst ecosystem - Chen Ran; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Yue Cao; Luhua Wu; Fei Chen; Chaojun Li; Xuling Luo; Min Liu; Sirui Zhang (Science of The Total Environment, 2023)

Sediment provenance and dispersal in the early Eocene Dongying Depression, Bohai Bay Basin, Eastern China: Evidence from detrital zircon geochronology, geochemistry and petrology - Ke Yang; Xiaomin Zhu; Luca Colombera; Adam McArthur; Nigel P. Mountney; Shifa Zhu; Lei Jin; Tingting Shen; Huaiyu Yang; Hongkui Chen; Shuanghui Xie; Xuling Jin (Sedimentary Geology, 2023)

Co-treatment of municipal solid waste incineration fly ash (MSWI FA) and municipal sludge: A innovative method to improve sludge dewatering with fly ash dechlorination - Jinxin Xing; Qingyu Tang; Min Gan; Zhiyun Ji; Xiaohui Fan; Zengqing Sun; Xuling Chen (Journal of Environmental Management, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Investigation on the application of by-product steam in iron ore sintering: performance and function mechanism - Yufeng Wu; Xiaohui Fan; Zhiyun Ji; Min Gan; Haoyu Zhou; Haorui Li; Xuling Chen; Yuanjie Zhao; Rongchang Zhang; Ruisi Lai (Environmental Science and Pollution Research, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

A New Indicator for Global Food Security Assessment: Harvested Area Rather Than Cropland Area - Fengjiao Song; Shijie Wang; Xiaoyong Bai; Luhua Wu; Jinfeng Wang; Chaojun Li; Huan Chen; Xuling Luo; Huipeng Xi; Sirui Zhang; Guofeng Luo; Mengqi Yan; et al. (Chinese Geographical Science, 2022)

The effects of Japanese encephalitis virus antibodies on Zika virus infection - Xiaoen He; Xinyue Lang; Jianhai Yu; Li Zhu; Zhiran Qin; Xuling Liu; Pei Chen; Chengguqiu Dai; Tingting Chen; Xujuan Li; Yangyang Chen; Dongrui Zhou; et al. (Medical Microbiology and Immunology, 2020)

Influences of fine-grained NaCl particles on performance and denitration efficiency of activated carbon during sintering flue gas purification process - Xiaohui Fan; Jiawen Yao; Min Gan; Wei Lv; Zhiyun Ji; Xuling Chen; Guojing Wong; Qingyu Tang (Environmental Science and Pollution Research, 2019)

Epithelial sodium channel enhanced osteogenesis via cGMP/PKGII/ENaC signaling in rat osteoblast - Jun Chen; Hengjie Zhang; Xuling Zhang; Guozhu Yang; Li Lu; Xingyan Lu; Chao Wan; Kosei Ijiri; Honglong Ji; Qingnan Li (Molecular Biology Reports, 2014)

Evaluation on tourism ecological security in nature heritage sites —Case of Kanas nature reserve of Xinjiang, China - Xuling Liu; Zhaoping Yang; Feng Di; Xuegang Chen (Chinese Geographical Science, 2009)

Biological control of fusarium head blight of wheat with Clonostachys rosea strain ACM941 - Allen Xue; Yuanhong Chen; Harvey Voldeng; Marc Savard; Xuling Tian (Cereal Research Communications, 2008)

Empirical analysis of Xinjiang’s bilateral trade: Gravity model approach - Xuegang Chen; Zhaoping Yang; Xuling Liu (Chinese Geographical Science, 2008)